A survey on lean manufacturing implementation in a selected manufacturing industry in Iran - Zahraee, Seyed Mojib (Emerald Group Publishing Ltd., 2016)
Lean manufacturing (LM) practices and tools are among the key concepts that assist managers and engineers sustain competitiveness in an expanding global market. The purpose of this paper is to identify effective practices and tools of lean manufacturing implementation in an Iranian manufacturing industry. Design/methodology/approach – This study used a quantitative method. Stratified random sampling and self-administrated questionnaires were sent to respondents in an Iranian manufacturing industry. Findings – The final results indicate that processes and equipment, planning and control, supplier relationship, human resources and customer relations are significant practices in lean manufacturing in Iranian manufacturing factories. The results from this survey additionally show that lean tools such as Kaizen, 5S, setup time reduction, cellular manufacturing, continuous flow, equipment layout, product design simplicity and error proof equipment are crucial to lean manufacturing implementation. Research limitations/implications – This study focused solely on a manufacturing industry in Iran that deals with electrical, electronic, metal, plastic, rubber and other automotive components. Practical implications – The findings of this study emphasize some implications and suggest that reducing cost is more effective and decreased inventory is less effective on lean manufacturing implementation. The current study results should assist quality mangers, product managers and director managers as well as academicians. Originality/value – An investigation was carried out in this study based on the current situation of Iran’s manufacturing industry to empirically examine and evaluate the effect of lean practices and tools. Besides, a very limited number of studies have been done regarding the implementation of lean thinking and practices in Iran’s manufacturing industry.